The thermal expansion of (Fe1−yNiy)Si. (24th July 2017) - Hunt, Simon A; Wann, Elizabeth T H; Dobson, David P; Vočadlo, Lindunka; Wood, Ian G
Abstract: We have measured the thermal expansion of (Fe1− y Ni y )Si for y = 0, 0.1 and 0.2, between 40 and 1273 K. Above 700 K the unit-cell volumes of the samples decrease approximately linearly with increasing Ni content. Below 200 K the unit-cell volume of FeSi falls to a value between that of (Fe0.9 Ni0.1 )Si and (Fe0.8 Ni0.2 )Si. We attribute this extra contraction of the FeSi, which is a narrow band-gap semiconductor, to the depopulation of the conduction band at low temperatures; in the two alloys the additional electrons introduced by the substitution of Ni lead to the conduction band always being populated. We have fit the unit-cell volume data with a Debye internal energy model of thermal expansion and an additional volume term, above 800 K, to take account of the volumetric changes associated with changes in the composition of the sample. Using the thermophysical parameters of the fit we have estimated the band gap in FeSi to be 21(1) meV and the unit-cell volume change in FeSi associated with the depopulation of the conduction band to be 0.066(35) Å 3 /unit-cell.